Cell-wall chemical-composition analysis of a Saccharum spp. progeny for increased bagasse digestibility - Garcia, José María; Acevedo, Alberto; Silva, M.P.; Gomez, L.; Erazzu, Luis Ernesto (International Society of Sugar Cane Technologists, 2021)
XXX Congress of the ISSCT (International Society of Sugar Cane Technologists), Tucumán, from 31 August to 8 September 2019